Factors attracting the inflow of foreign workers to Malaysia construction industry - Ariana, Anak Henry Peros (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Study Objective:(an increasing numbers of foreign workers resulted from strong economic growth that recorded employment creation added on jobs and all major sectors saw on employment growth. This research attempts to highlight on factors attracting the inflow of foreign workers to Malaysia construction industry such as total employment, Malaysia gross domestic products and wag, Design/methodology/approach: A regression analysis is conducted using secondary data from 1982 to 2012 in order to determine factors attracting the inflow of foreign workers to Malaysia construction industry. Findings: The study is conducted using Eviews 7.0 by using Unit Root Test, Johansen Co Integration Test and Granger Causality test to determine factors attracting the inflow of foreign workers to Malaysia construction industry. Results: The results demonstrate a significant relationship between independent variables such as total employment, Malaysia gross domestic product and wages with the dependent variable inflow of foreign workers in Malaysia construction industry.